Thirty Years after the Council: The Catholic Church in The Philippines' Reception of PCP II and Remembrance of Martial Law - Cortez, Kenjie I. (Archīum Ateneo, 2023)
2021 was a momentous time for the Catholic Church in the Philippines as it commemorated the thirtieth anniversary of the Second Plenary Council of the Philippines (PCP II).2 Nonetheless, the following year was in no way inconsequential because it marked both thirty years since the promulgation of the Council's Decrees and fifty years since the declaration of martial law. While one may find this a sheer coincidence, one must not forget that the country’s martial law experience significantly shaped PCP II’s and its vision of renewal for the Philippine Church.3 With the election of the dictator’s son and namesake to the presidency in 2022, one may wonder if the country’s collective memory of its recent past has anything to do with the reception of PCP II and vice versa. Hence, the aim of this paper is twofold. First, it argues that the Philippine Church’s initial reception of Vatican II is tied to its experience of the dictatorial regime. Second, it articulates how the foundations and strengths of PCP II’s ecclesiology capture the spirit of the EDSA People Power Revolution.